Explicit Instruction in Metacognitive Problem-Solving Reading Strategies: Developing Reading Comprehension and Strategy Use - Mouchrif, Hassan; Mokhtari, Najat; Benzehaf, Bouchaib (Universitas Syiah Kuala, 2025)
This study examined the impact of Problem-solving Reading Strategies (PROBs), a specific subset of Metacognitive Reading Strategies (MRSs), on reading comprehension and strategy use among young Moroccan EFL learners. The first phase focused on assessing the feasibility of explicitly teaching PROBs to young learners, while the second phase examined the effects of PROBs on their reading comprehension and strategy use. The study involved 31 young EFL learners enrolled at a Moroccan EFL center, who were randomly assigned to an experimental group and a control group. Data were collected using measures of reading comprehension and strategy use, including the Metacognitive Awareness of Reading Strategies Inventory by Mokhtari and Reichard (MARSI, 2002). Data analysis using independent t-tests demonstrated that explicit PROB instruction is feasible when delivered through metacognitive scaffolding and structured PROB-based programs. This feasibility was reflected in the positive responses of students to the intervention. Moreover, the experimental group significantly improved their reading comprehension scores, achieving a p-value of 0.04 (p 0.05), indicating their enhanced ability to solve comprehension problems and maintain overall text comprehension. The intervention also elevated the students' strategy use, transforming them into active PROB users. These findings carry important implications for both educators and curriculum designers, highlighting the potential of PROB-focused instruction in improving EFL literacy outcomes.